Application of CRISPR/Cas9 Technology in Cancer Treatment: A Future Direction. - Rabaan, Ali A.; AlSaihati, Hajir; Bukhamsin, Rehab; Bakhrebah, Muhammed A.; Nassar, Majed S.; Alsaleh, Abdulmonem A.; Alhashem, Yousef N.; Bukhamseen, Ammar Y.; Al-Ruhimy, Khalil; Alotaibi, Mohammed; Alsubki, Roua A.; Alahmed, Hejji E.; et al. (Current Oncology, 2023)
Gene editing, especially with clustered regularly interspaced short palindromic repeats associated protein 9 (CRISPR-Cas9), has advanced gene function science. Gene editing's rapid advancement has increased its medical/clinical value. Due to its great specificity and efficiency, CRISPR/Cas9 can accurately and swiftly screen the whole genome. This simplifies disease-specific gene therapy. To study tumor origins, development, and metastasis, CRISPR/Cas9 can change genomes. In recent years, tumor treatment research has increasingly employed this method. CRISPR/Cas9 can treat cancer by removing genes or correcting mutations. Numerous preliminary tumor treatment studies have been conducted in relevant fields. CRISPR/Cas9 may treat gene-level tumors. CRISPR/Cas9-based personalized and targeted medicines may shape tumor treatment. This review examines CRISPR/Cas9 for tumor therapy research, which will be helpful in providing references for future studies on the pathogenesis of malignancy and its treatment.